Failure mechanism analysis of fuses subjected to manufacturing and operational thermal stresses. (September 2018) - Bahman, A.S.; Jensen, S.M.; Iannuzzo, F.
Abstract: This paper identifies failure mechanisms of axial lead fuses subjected to real field ambient thermal profiles by finite element simulations and experimental testing. Experimental observation of failed fuses attributes fatigue failure of fuses to breakage of the fuse element. The fuse elements consistently fail at the notches adjacent to the end caps accompanied by a localized out-of-plane bend. Identification of the failure mechanism motivates a comprehensive thermo-mechanical study of the fuse deformation response prior to failure, which is rather involved due to the complex interactions of the fuse components, and residual effects of manufacturing processes. An investigation on the pre-operational state of fuses evaluates damage introduced during manufacturing of the fuse. In specific, the work simulates soldering induced residual stresses and addresses their impact on the fatigue damage and lifetime of the fuse. In the paper a lifetime model of the fuse is proposed and tested. Highlights: Failure mechanisms of fuses subjected to real field thermal profiles have been identified by finite element simulations. Experimental observation of failed fuses attributes fatigue failure of fuses to breakage of the fuse element. The fuse elements consistently fail at the notches adjacent to the end caps accompanied by a localized out-of-plane bend. An investigation on the pre-operational state of fuses evaluates damage introduced during manufacturing of the fuse. In specific, soldering induced residual stresses impact on the fatigue damage and lifetime of the fuse. A lifetime model of the fuse is proposed and tested.